Interpreting Primo Levi Interdisciplinary Perspectives - Vuohelainen, Minna; Chapman, Arthur; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
The legacy of antifascist partisan, Auschwitz survivor, and author Primo Levi continues to drive exciting interdisciplinary scholarship. The contributions to this intellectually rich, tightly organized volume - from many of the world's foremost Levi scholars - show a remarkable breadth across fields as varied as ethics, memory, and media studies.
Keywords: Science; Science; Science, general; Electronic books